Predictive indicators of success in science & engineering projects - application to the SKA initiative - Crosby, Philip (Curtin University, 2012)
Projects that have scientific goals and are characterised by new engineering technologies, significant infrastructure, and big budgets are typically found to undergo much scrutiny prior to approval. What is less clear is whether concept reviews, approval, funding, or early stage planning takes proper advantage of potential indicators of success based on learnings from relevant past experience. In other words, is the likelihood of success in meeting all project goals considered at the outset, and can early stage project development/planning be made more effective?Through examination of published literature, interviews with past and present project managers, scientists and engineers, and investigation of selected case studies in Australia, Chile, South Africa and Europe, this thesis attempts to (i) identify critical success factors relevant to large, complex high-technology projects, (ii) investigate the use of experience as success indicators within contemporary case studies, and (iii) distil the results into a set of predictive test indicators of likely project success.While there is considerable literature concerning general management of large projects, and covering execution of complex undertakings, there is little specific material dealing with success drivers for large and complex high-technology projects. This thesis aims to fill this important gap in the current understanding.The present study distils an epistemic view of high-technology ‘mega-projects’, and through case examination and inductive and deductive reasoning, shows that serious attention paid to specific aspects of project-shaping can lift the probability of success. An additional output is a practical checklist tool for ‘high-tech’ mega-project practitioners.The findings from this research have direct applicability to current and future approvers and managers of large scale high-technology projects, and in particular the Square Kilometre Array (SKA) radio telescope project to be built in either Australasia or Southern Africa, and planned to commence preconstruction in 2012.